The Effects of FoMO on Student Consumption Behavior in the Digital Economy Era - Husna , Jihan Arifah; Wiranatakusuma, Dimas Bagus; Anggi Aprizal (Jurnal Manajemen, Akuntansi, Ekonomi, 2025)
The rapid rise of digital platforms, particularly TikTok, has significantly influenced consumer behavior. It causes the emergence of FOMO (Fear of Missing Out) as a key driver of impulsive purchasing. This study aims to investigate the effects of FoMO on student consumption behavior in this digital economy, focusing on students at Muhammadiyah University of Yogyakarta (UMY). Using a qualitative approach with a cross-sectional design, data were collected through semi-structured interviews with three UMY students who actively shop on TikTok. The findings reveal that FoMO leads to impulsive buying, driven by emotional triggers such as trends, live-streaming promotions, discounts, and free shipping. Furthermore, some students already have budgeting awareness related to FoMO purchases, while others still face financial management challenges. Additionally, feelings of guilt were identified as a secondary effect, often stemming from dissatisfaction with impulsive purchases. The study highlights the role of TikTok in amplifying FoMO-driven consumption and underscores the need for awareness to do budgeting. These findings offer insights among students to foster their mindfulness of consumption habits in this digital era.